Plant growth-promoting microorganisms as biocontrol agents of plant diseases: Mechanisms, challenges and future perspectives - El-Saadony, Mohamed T.; Saad, Ahmed M.; Soliman, Soliman M.; Salem, Heba M.; Ahmed, Alshaymaa I.; Mahmood, Mohsin; El-Tahan, Amira M.; Ebrahim, Alia A. M.; Abd El-Mageed, Taia A.; Negm, Shaimaa H.; Selim, Samy; Babalghith, Ahmad O.; et al. (Frontiers in Plant Science, 2022)
Plant diseases and pests are risk factors that threaten global food security. Excessive chemical pesticide applications are commonly used to reduce the effects of plant diseases caused by bacterial and fungal pathogens. A major concern, as we strive towards more sustainable agriculture, is to increase crop yields for the increasing population. Microbial biological control agents (MBCAs) have proved their efficacy to be a green strategy to manage plant diseases, stimulate plant growth and performance, and increase yields. Besides their role in growth enhancement, plant growth-promoting rhizobacteria/fungi (PGPR/PGPF) could suppress plant diseases by generating pathogen-antagonizing chemicals and inducing immune responses in plants. As biofertilizers and biopesticides, PGPR and PGPF are considered as feasible, attractive economic approach for sustainable agriculture; thus, resulting in a “win-win” situation. Several PGPR and PGPF strains have been identified as effective BCAs under environmentally controlled conditions. In general, any MBCA must overcome certain challenges before it can be registered or widely utilized to control diseases/pests. Successful MBCAs, as antagonists and BCAs, offer a practical solution to improve greenhouse crop performance with reduced fertilizer inputs and chemical pesticide applications. This review aims to fill the gap in the current knowledge of plant growth-promoting microbes (PGPM), provide attention about the scientific basis for policy development, and recommend further research related to the applications of PGPM used for commercial purposes.